The Influence of Work Stress, Role Conflict and Emotional Exhaustion on Organizational Commitment at PT. Vinsia Bingkai Medan - Julianto, Fajar; Imelda, Sarah; Tamba, Muller (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the effect of work stress, role conflict, and emotional exhaustion on organizational commitment at PT. Vinsia Bingkai, Medan. The method used in this study is multiple linear regression analysis involving 102 respondents. The results of the study indicate that work stress and role conflict have a positive and significant effect on organizational commitment, with significance values ​​of 0.048 and 0.036, respectively. On the other hand, emotional exhaustion does not show a significant effect on organizational commitment, with a significance value of 0.494. This study concludes that management needs to pay attention to work stress and role conflict factors to increase employee commitment, while emotional exhaustion needs to be managed so as not to interfere with employee performance. These findings are expected to provide insight for management in formulating better strategies to increase organizational commitment in the company.